Pengaruh Disiplin Kerja, Fasilitas Kerja dan Motivasi, terhadap Produktivitas Pegawai pada Kantor Kesatuan Bangsa dan Politik Kabupaten Labuhanbatu - Fitri Indah Lestari; Nurintan Asyiah Siregar; Zulkifli Musannif (Neolectura, 2022)
This study aims to determine the effect of work discipline, work facilities, motivation on employee productivity at the Office of the National Unity and Politics of Labuhanbatu Regency. The sample used in this study were all employees, totaling 30 employees. Data collection method using Likert Scale. Based on the results of the partial study (T test) it shows that Work Discipline (X1) has a positive and significant effect on Employee Productivity (Y) at the National and Political Unity Office of Labuhanbatu Regency with tcount 2,219 > ttable 1,705 with a significant level of 0.035 < 0, 05. Work Facilities (X2) have a positive and significant effect on Employee Productivity (Y) at the National and Political Unity office in Labuhanbatu Regency, with a tcount of 3.982 > ttable 1.705 with a significant level of 0.000 <0.05. Motivation (X3) has no positive and significant effect on Employee Productivity (Y) at the National and Political Unity office of Labuhanbatu Regency, with tcount 1.062 < ttable 1.705 with a significant level of 0.298> 0.05. Based on the simultaneous test (Test F) shows that Work Discipline, Work Facilities, and Motivation simultaneously have a positive and significant effect on Employee Productivity at the Office of the National Unity and Politics of Labuhanbatu Regency, with an Fcount of 5.390 > Ftable 2.96 with a significant level of 0.005 < 0.05. Based on the results of the R Square Coefficient Test, it shows that the variable of Employee Productivity at the Office of the National Unity and Politics of Labuhanbatu Regency can be explained by the variables of Work Discipline, Work Facilities, and Motivation of 38.3% while the remaining 61.7% is influenced by other factors that not investigated in this study.